PENGARUH CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA XL DI KOTA BOGOR - Restu Oktafiani; Endang Silaningsih (Jurnal Visionida, 2015)
XL Axiata Company engaged in the field of mobile phone operators in marketing their products XL Axiata using celebrity endorser that aims to increase the number of customers through the sale of starter packs. The method used is survey method, to form descriptive research, verification. The object of this study is the XL card in Bogor with a sample of 100 respondents, data was collected through questionnaires and interviews. Test instruments made with validity and reliability as well as assumptions UJIA classic analysis methods include multiple regression analysis, correlation and significance tests simultaneously and partially. The results of this study all valid and reliable indicators, simultaneously Credibility (X1), attractiveness (X2 ) and power (X3) influence on purchase decisions XL card (Y) while Partially attribute credibility (X1), attractiveness (X2) significant and positive impact on purchasing decisions XL card, whereas power (X3) is not significant and positive impact on purchase decisions XL card. Credibility (X1), attractiveness (X2) is a contributing factor in this study, while power (X3) is an inhibiting factor.Keywords: Celebrity Endorser, Purchase Decision